Self-Regulation of Cerebral Metabolism and Its Neuroprotective Effect After Hypoxic-Ischemic Injury: Evidence From 1H-MRS - Li, Kexin; Zheng, Yang; Wang, Xiaoming (Frontiers in Neuroanatomy, 2021)
1H-MRS technology can be used to noninvasively detect the content of cerebral metabolites, to assess the severity of hypoxic-ischemic (HI) injury, and to predict the recovery of compromised neurological function. However, changes to the cerebral self-regulation process after HI are still unclear. This study investigated the changes in cerebral metabolites and the potential relationship with the number of neurons and neural stem/progenitor cells (NSPC) using 1H-MRS, and finally clarifies the self-regulation of cerebral metabolism and neuroprotection after HI injury. Newborn Yorkshire pigs (28 males, 1.0–1.5 kg) aged 3–5 days were used for the HI model in this study. The pigs were randomly divided into the HI group (n = 24) and the control group (n = 4), then the experimental group was subdivided according to different recovery time after HI into the following groups: 0–2 h (n = 4), 2–6 h (n = 4), 6–12 h (n = 4), 12–24 h (n = 4), 24–48 h (n = 4), and 48–72 h (n = 4). Following the HI timepoints, 1H-MRS scans were performed and processed using LCModel software, and brain tissue was immunohistochemically stained for Nestin and NeuN. Immunofluorescence staining of creatine phosphokinase-BB (CK-BB), N-acetylaspartylglutamate synthetase (NAAGS), glutamate carboxypeptidase II (GCP-II), glutamate-cysteine ligase catalytic subunit (GCLC), glutathione synthase (GS), and excitatory amino acid carrier 1 (EAAC1) was then performed. The 1H-MRS results showed that cerebral N-acetylaspartylglutamate (NAAG), glutathione (GSH), and creatine (Cr) content reached their peaks at 12–24 h, which was consistent with the recovery time of hippocampal NSPCs and neurons, indicating a potential neuroprotective effect of NAAG, GSH, and Cr after HI injury.